Pure laparoscopic radical nephroureterectomy for complicated renal pelvis carcinoma combined with horseshoe kidney: A case report and literature review - Huang, Ruizhen; Tian, Jie; Jiang, Weifan (Frontiers in Oncology, 2022)
We reported a case of pure laparoscopic radical nephroureterectomy for complicated renal pelvis carcinoma combined with horseshoe kidney (HSK). The aim was to present a case report and review of the literature about renal pelvis carcinoma combined with HSK. The case report includes a history of patient data. The pure laparoscopic radical nephroureterectomy was provided with the informed consent of the patient. A 53-year-old patient was diagnosed with a right renal pelvis mass with HSK. We performed laparoscopic radical nephroureterectomy with partial cystectomy and horseshoe renal isthmus amputation. Histopathological features, computed tomography urography (CTU), and angiography (CTA) confirmed the diagnosis of renal pelvis carcinoma combined with HSK. The tumor was removed, and the patient made an uneventful recovery. Renal pelvis carcinoma combined with HSK is a rare case. Due to severe anatomical abnormalities, this disease is a major challenge for urologists. We share our successful case for readers to learn from.